QUALITATIVE RESEARCH IN REGIONAL GEOGRAPHY. A METHODOLOGICAL APPROACH - ILOVAN, Oana-Ramona; DOROFTEI, Iulia (Presa Universitară Clujeană, 2017)
The aim of this book is to encourage Romanian students and geographers to take an interest in qualitative research. It answers a need in the Romanian university geographical system: that of exploring the role of qualitative research methods and their usefulness and relevance both for research and for university students’ professional training. Given the fact that, for a very long time, Romanian geographers used the descriptive method and the quantitative ones, very often not trusting the qualitative methods and the results obtained with such “subjective” methodology, a pro domo book like this volume is necessary.